Development and validation of a nomogram to predict acute postoperative urinary retention in ischemic stroke patients following femoral artery puncture - Zhu, Minfang; Zhang, Weibin; Lyu, Anqi; Gao, Juanbi (Frontiers in Neurology, 2024)
Background: Acute postoperative urinary retention (POUR) is a common complication in patients with ischemic stroke following femoral artery puncture (FAP), leading to discomfort, delayed hospital discharge, and increased patient morbidity. The relevant risk factors are unclear; thus, a predictive tool is required to guide treatment decisions. Objective: To develop and validate a nomogram to predict acute POUR in patients with ischemic stroke following FAP. Methods: We retrospectively collected cases from 1729 patients with ischemic stroke from the electronic record system of Jiangmen Central Hospital from January 2021 to December 2023. A total of 731 patients were randomly divided into development (n = 511, 70%) and validation (n = 220, 30%) groups. Univariate and multivariate logistic regression analyses with backward stepwise regression were used to select the predictive variables, and a nomogram was developed. The discrimination was evaluated based on the area under the curve (AUC). Calibration was assessed using calibration plots and the Hosmer–Lemeshow test. Clinical applications were evaluated using decision curve analysis (DCA). Results: The incidence of acute POUR was 12.72%. Preoperative statin use within 24 h, operation type, intraoperative infusion, postoperative water intake within 3 h, postoperative pain, and postoperative anxiety were included in the nomogram. The AUC values were 0.764 (95% confidence interval (CI): 0.705–0.825) in the development group and 0.741 (95% CI: 0.615–0.856) in the validation group. The calibration plots showed good calibration. The p values in the Hosmer–Lemeshow tests were 0.962 and 0.315 for the development and validation groups, respectively. The DCA showed that patients could benefit from this nomogram. Conclusion: A nomogram was developed to successfully predict acute POUR in patients with ischemic stroke following FAP. This nomogram is a convenient and effective tool for clinicians to aid in the prevention and early intervention of acute POUR.